Glutaminolysis and peripheral CD4+ T cell differentiation: from mechanism to intervention strategy - Liu, Tong; Ren, Shaohua; Sun, Chenglu; Zhao, Pengyu; Wang, Hao (Frontiers in Immunology, 2023)
To maintain the body's regular immune system, CD4 + T cell homeostasis is crucial, particularly T helper (Th1, Th17) cells and T regulatory (Treg) cells. Abnormally differentiated peripheral CD4 + T cells are responsible for the occurrence and development of numerous diseases, including autoimmune diseases, transplantation rejection, and irritability. Searching for an effective interventional approach to control this abnormal differentiation is therefore especially important. As immunometabolism progressed, the inherent metabolic factors underlying the immune cell differentiation have gradually come to light. Mounting number of studies have revealed that glutaminolysis plays an indelible role in the differentiation of CD4 + T cells. Besides, alterations in the glutaminolysis can also lead to changes in the fate of peripheral CD4 + T cells. All of this indicate that the glutaminolysis pathway has excellent potential for interventional regulation of CD4 + T cells differentiation. Here, we summarized the process by which glutaminolysis regulates the fate of CD4 + T cells during differentiation and further investigated how to reshape abnormal CD4 + T cell differentiation by targeting glutaminolysis.